2010
DOI: 10.1007/s00122-010-1421-7
|View full text |Cite
|
Sign up to set email alerts
|

A core collection and mini core collection of Oryza sativa L. in China

Abstract: The extent of and accessibility to genetic variation in a large germplasm collection are of interest to biologists and breeders. Construction of core collections (CC) is a favored approach to efficient exploration and conservation of novel variation in genetic resources. Using 4,310 Chinese accessions of Oryza sativa L. and 36 SSR markers, we investigated the genetic variation in different sized sub-populations, the factors that affect CC size and different sampling strategies in establishing CC. Our results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
150
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(154 citation statements)
references
References 25 publications
4
150
0
Order By: Relevance
“…According to six diagnostic characters, Cheng (1985) further classified Chinese rice into Hsein, Hsein-cline, Keng-cline and Keng, whereas Ting (1957) developed a five-level taxonomic system for Chinese germplasm, in which rice cultivars were divided into Hsien and Keng subspecies, two seasonal types (early/medium and late sown), two drought-tolerant (or watery regime) types (lowland and upland) and two endosperm types (waxy and non-waxy) and other cultivars. In addition to the Hsien and Keng classification, the other four types of divisions were mainly based on ecological or habitat features and were not supported by subsequent investigations, particularly molecular approaches (Zhang et al, 2009(Zhang et al, , 2011a. By screening 3024 Chinese landraces, for example, Zhang et al (2009) found clear differentiation within two subspecies, that is, the subdivision among seasonal types within Indica and differentiation between drought-tolerant types within Japonica.…”
Section: Diversity and Differentiation Of Chinese Rice Cultivarsmentioning
confidence: 89%
See 3 more Smart Citations
“…According to six diagnostic characters, Cheng (1985) further classified Chinese rice into Hsein, Hsein-cline, Keng-cline and Keng, whereas Ting (1957) developed a five-level taxonomic system for Chinese germplasm, in which rice cultivars were divided into Hsien and Keng subspecies, two seasonal types (early/medium and late sown), two drought-tolerant (or watery regime) types (lowland and upland) and two endosperm types (waxy and non-waxy) and other cultivars. In addition to the Hsien and Keng classification, the other four types of divisions were mainly based on ecological or habitat features and were not supported by subsequent investigations, particularly molecular approaches (Zhang et al, 2009(Zhang et al, , 2011a. By screening 3024 Chinese landraces, for example, Zhang et al (2009) found clear differentiation within two subspecies, that is, the subdivision among seasonal types within Indica and differentiation between drought-tolerant types within Japonica.…”
Section: Diversity and Differentiation Of Chinese Rice Cultivarsmentioning
confidence: 89%
“…We also calculated the F ST value between three subgroups within Chinese Indica and found relatively low differentiation between them (F ST ¼ 0.076-0.132), consistent with the finding that subdivision was less apparent within Chinese Indica. We further estimated the genetic diversity of the 184 Chinese cultivars that were identified to belong to the core collection (Zhang et al 2011a). We found that the number of alleles in the core collection is lower than that in total samples, particularly for tropical japonica (9.5 vs 5.5).…”
Section: Level and Organization Of Genetic Diversity Of Rice Cultivarsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the population used for association mapping consisted of 303 cultivated rice varieties in a rice mini core collection (including 204 Chinese varieties [22] and 99 varieties from other countries, Table S1). The awnness of each variety was evaluated in Sanya (18°09′N) and Hangzhou (29°44′N) in 2006 and in Beijing (39°56′N) in 2009.…”
mentioning
confidence: 99%